2015
DOI: 10.1016/j.bpj.2014.11.3462
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Detection and Analysis of Exocytosis Reveal Fusion “Hotspots” Organized by the Cytoskeleton in Endocrine Cells

Abstract: Total internal reflection fluorescence microscope has often been used to study the molecular mechanisms underlying vesicle exocytosis. However, the spatial occurrence of the fusion events within a single cell is not frequently explored due to the lack of sensitive and accurate computer-assisted programs to analyze large image data sets. Here, we have developed an image analysis platform for the nonbiased identification of different types of vesicle fusion events with high accuracy in different cell types. By p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 52 publications
5
63
1
Order By: Relevance
“…Quantitative imaging of SNAP-25 and Lifeact-GFP revealed that these structures overlap in a significant manner indicating association of components of the secretory machinery to the F-actin cortex. In agreement with these data Yuan et al (Yuan et al, 2015) found evidence of fusion hotspots in insulin-secreting INS-1 cells, whose organization relies on the cytoskeleton. Using TIRF microscopy they found that individual fusion events are clustered and that this clustering disappears upon inhibition of either the actin or microtubule network.…”
Section: Cytoskeleton-dependent Compartmentalised Lipid Diffusionsupporting
confidence: 77%
“…Quantitative imaging of SNAP-25 and Lifeact-GFP revealed that these structures overlap in a significant manner indicating association of components of the secretory machinery to the F-actin cortex. In agreement with these data Yuan et al (Yuan et al, 2015) found evidence of fusion hotspots in insulin-secreting INS-1 cells, whose organization relies on the cytoskeleton. Using TIRF microscopy they found that individual fusion events are clustered and that this clustering disappears upon inhibition of either the actin or microtubule network.…”
Section: Cytoskeleton-dependent Compartmentalised Lipid Diffusionsupporting
confidence: 77%
“…The second possibility is that dynamin-induced actin reorganization retards granule recruitment at a later stage of secretion. This is supported by the positive role of actin in vesicle transport (64)(65)(66)(67) and the pronounced defect in the second-phase secretion (Figure 3), which largely relies on new granule recruitment to the PM (8,11). To directly test this idea, we incubated β cells for 1 hour with 20 mM glucose and 10 nM glucagon-like peptide-1 (GLP-1), an incretin peptide that increases insulin secretion through cAMPand VAMP8-dependent mechanisms (68).…”
Section: And E)mentioning
confidence: 98%
“…Alignment of two-color images, semi-automated vesicle-fusion detection, and spatiotemporal averaging of local fluorescence signals from multiple events were done using a self-written program in MATLAB (MathWorks) (Yuan et al, 2015). A 5-pixel (335-nm) diameter circle that encloses the center of a fusion spot was selected to calculate the average fluorescence signal of VAMP2-pHluorin.…”
Section: Imaging Data Analysismentioning
confidence: 99%